Application Of the Expository Learning Method In Understanding The Perception Of Hijaiyah Letter Forms In 'Mild Mentally Retarded' Students At SLB YPLB-LB Hegar Asih - Zul Andrivat; Aan Hasanah; Badrudin Badrudin; Dewi Sadiah (Yayasan Azka Hafidz Maulana, 2026)
This research is motivated by the low abilities of students with special needs, especially those classified as